2018
DOI: 10.1029/2017wr022353
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Use of Seabed Sediment Temperature Profiles to Trace Submarine Groundwater Flow

Abstract: Submarine groundwater fluxes across the seafloor facilitate important hydrological and biogeochemical exchanges between oceans and seabed sediment, yet few studies have investigated spatially distributed groundwater fluxes in deep‐ocean environments such as continental slopes. Heat has been previously applied as a submarine groundwater tracer using an analytical solution to a heat flow equation assuming steady state conditions and homogeneous thermal conductivity. These assumptions are often violated in shallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Conversely, the upward movement of lower-density groundwater (e.g., as expected to arise during SFGD) is rarely explored in the solute transport context, although upward, buoyancy-driven groundwater flow has received significant attention in the field of heat transport and geothermal phenomena. For example, Kurylyk et al (2018) utilized temperature-based methods to quantify submarine groundwater fluxes in seafloor sediments offshore of eastern Canada. However, their study suggested that the flow patterns inferred from seafloor temperature-depth profiles appear to be influenced by both density-driven and geothermal processes.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the upward movement of lower-density groundwater (e.g., as expected to arise during SFGD) is rarely explored in the solute transport context, although upward, buoyancy-driven groundwater flow has received significant attention in the field of heat transport and geothermal phenomena. For example, Kurylyk et al (2018) utilized temperature-based methods to quantify submarine groundwater fluxes in seafloor sediments offshore of eastern Canada. However, their study suggested that the flow patterns inferred from seafloor temperature-depth profiles appear to be influenced by both density-driven and geothermal processes.…”
Section: Introductionmentioning
confidence: 99%
“…Seabed TD profiles in these settings are often curved and thus not linear as expected under conduction‐dominated, homogeneous, and steady‐state conditions. Several studies have attributed this curvature to the impacts of groundwater flow (Figure b) and have quantified submarine groundwater fluxes or geothermal circulation based on steady‐state thermal groundwater tracing methods described in Section 3 (Abbott & Menke, , ; R. N. Anderson, Hobart, & Langseth, ; Fisher & Becker, ; Geller, Weissel, & Anderson, ; Kurylyk et al, ; Wheat et al, ). However, such analyses can yield highly uncertain vertical groundwater fluxes because TD curvature may also be attributed to other factors such as vertical variations in seabed thermal conductivity and low‐frequency bottom water temperature changes (Noel, ).…”
Section: Interdisciplinary Nature Of Thermal Groundwater Tracingmentioning
confidence: 99%
“…The estimation of q using Equation relies on the deviation of a TD profile from a linear relationship. The maximum deviation ( Δ max ) is (Kurylyk et al, ): Δmax=()TLT0{}exp()β1ββexp()ββln[]expβ1β1β. …”
Section: Steady‐state Approaches For Analyzing Td Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat has been widely applied to trace groundwater-surface water exchanges in inland surface water bodies such as streams, rivers, and lakes as detailed in prior reviews (Constantz, 2008;Irvine et al, 2017;Kurylyk et al, 2019;Rau et al, 2014). However, these methods have only rarely been applied in tidal estuaries (Befus et al, 2013;Henderson et al, 2009), lagoons (Swain & Prinos, 2018;Tirado-Conde et al, 2019) or offshore environments (Goto et al, 2005;Kurylyk et al, 2018;Wilson et al, 2016). To our knowledge, previous studies have not directly addressed the influence of tide-driven oscillations in vertical water fluxes when using conventional heat as a tracer techniques.…”
mentioning
confidence: 99%